2002
DOI: 10.1038/sj.bjp.0704499
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous phasic activity of the pig urinary bladder smooth muscle: characteristics and sensitivity to potassium channel modulators

Abstract: 1 A hallmark for unstable bladder contractions is hyperexcitability and changes in the nature of spontaneous phasic activity of the bladder smooth muscle. In this study, we have characterized the spontaneous activity of the urinary bladder smooth muscle from the pig, a widely used model for studying human bladder function. 2 Our studies demonstrate that phasic activity of the pig detrusor is myogenic and is in¯uenced by the presence of urothelium. Denuded strips exhibit robust spontaneous activity measured as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 33 publications
10
102
2
Order By: Relevance
“…Those other cell types include the endometrium which lies inside the myometrial smooth muscle of the uterus, the enteric nervous system which innervates the intestinal smooth muscle of the duodenum, and the urothelium which separates the detrusor smooth muscle of the bladder wall from the urine inside. But while these nonmuscular cells may be able to modulate spontaneous contractility of the adjacent smooth muscle cell layers (Gershon, 1981;Granger et al, 1986;Haynes and Pennefather, 1993;Buckner et al, 2002;Azadzoi et al, 2004;Bulbul et al, 2007;Kanai et al, 2007), they are not likely the primary site for gemfibrozil's relaxant effects. If, for example, gemfibrozil's relaxation of the duodenal contractility seen in Figure 5 were mediated solely by inhibition of enteric neuronal release of contractile neurotransmitters, then we would not expect to see its relaxant influence in uterus and bladder as well.…”
Section: Effects Of Gemfibrozil On Spontaneous Contractions Of Rat Utmentioning
confidence: 99%
See 1 more Smart Citation
“…Those other cell types include the endometrium which lies inside the myometrial smooth muscle of the uterus, the enteric nervous system which innervates the intestinal smooth muscle of the duodenum, and the urothelium which separates the detrusor smooth muscle of the bladder wall from the urine inside. But while these nonmuscular cells may be able to modulate spontaneous contractility of the adjacent smooth muscle cell layers (Gershon, 1981;Granger et al, 1986;Haynes and Pennefather, 1993;Buckner et al, 2002;Azadzoi et al, 2004;Bulbul et al, 2007;Kanai et al, 2007), they are not likely the primary site for gemfibrozil's relaxant effects. If, for example, gemfibrozil's relaxation of the duodenal contractility seen in Figure 5 were mediated solely by inhibition of enteric neuronal release of contractile neurotransmitters, then we would not expect to see its relaxant influence in uterus and bladder as well.…”
Section: Effects Of Gemfibrozil On Spontaneous Contractions Of Rat Utmentioning
confidence: 99%
“…uterus, duodenum and bladder. These tissues are known for their ability to exhibit spontaneously-occurring phasic rhythmic contractions, which are physiologically relevant and can be observed in vitro without the need to administer contractile agents (Small and Weston, 1971;Gershon, 1981;Granger et al, 1986;Leroy et al, 1991;Haynes and Pennefather, 1993;Buckner et al, 2002;Vedernikov et al, 2003;Azadzoi et al, 2004;Szigeti et al, 2005;Bulbul et al, 2007;Kanai et al, 2007). We determined if gemfibrozil inhibits these spontaneous activities.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary bladder contractility is also modulated by K ϩ efflux through SK channels (27,33,35), which contribute to the afterhyperpolarization of the urinary bladder smooth muscle action potential (12,21); blocking SK channels results in an increase in detrusor SPCs (9,27,33,35). To determine whether SK channel activity, like BK channel activity, was different between mucosal and detrusor myocytes, we first compared the effects of the SK channel blocker apamin (300 nM) on mucosal and detrusor smooth muscle SPCs.…”
Section: R358mentioning
confidence: 99%
“…Given the prominent role that BK channels play in regulating detrusor contractility (9,25,29,32,33,58,69), we sought to determine their role in the regulation of mucosal smooth muscle contractility. To assess the relative importance of BK channels in the regulation of mucosal smooth muscle SPCs, we tested the effects of the BK channel blocker IbTX (100 nM) on the SPCs of mucosal and detrusor tissue strips.…”
Section: R357mentioning
confidence: 99%
“…As previously reported (Buckner et al, 2002), spontaneous phasic activity was observed in many tissues that contracted with transient spikes that varied in frequency, duration, and amplitude. The tissue strips were exposed to varying concentrations of the test agents for 15 min and changes in contractility were assessed.…”
Section: Pig Bladder Relaxation Studiesmentioning
confidence: 55%